PEROSOMUS ELUMBIS IN SAHIWAL CALF: A CASE REPORT - MAHTO, DINESH; RANI, SHOBHA (The Indian Journal of Animal Reproduction, 2022)
A rare case of dystocia due to Perosomuselumbis in a cow and its successful per vaginum has been reported.
Keywords: PEROSOMUS ELUMBIS; SAHIWAL